On the contribution factors of enhanced photocatalytic activity of doped semiconductors: Structural and optical investigation of Cu2+ doped ZnO nanoparticles - Quynh, Ta Duy; Anh, Luu Thi Lan; Xuan, Nguyen Sang (Vietnam Journal of Science and Technology, 2021)
As a traditional direct bandgap oxide semiconductor, ZnO, showed as a promising photocatalytic candidate. Researchers worldwide reported many possibilities to improve its photocatalytic activity such as doped with metal, non-metal ions. As a result of heterojunction formation between ZnO and its intentional impurity, previous reports showed beneficial characteristics for enhancing photocatalytic activity in these ZnO-based materials, i.e. bandgap narrowing, recombination rate of photoelectron-hole prolonging, visible light absorption improving. This work will present the photocatalytic acitivity improvement of ZnO when doping with ion Cu2+ and try to illustrate the crucial photocatalytic enhancement factors.